2019
DOI: 10.1016/j.stem.2018.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Somatic Cell Reprogramming Involves Continuous Transcriptional Changes Governed by Myc and Epigenetic-Driven Modules

Abstract: Highlights d Unbiased high-resolution profiling of mouse deterministic reprogramming to naive iPSCs d Early DNA demethylation of pluripotency enhancers definitively marks future iPSCs d Myc activity is indispensable for conducive iPS formation from somatic cells d Optimized changes in tRNA codon usage amplify the output of Myc governed program

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 18 publications
2
59
0
Order By: Relevance
“…4f). This transient induction became even more apparent when we called H3K27ac peaks in two recent, independent iPSC reprogramming studies [74,75] (Fig. 4h-i).…”
Section: Starr-seq Reveals Endogenous Retrovirus Enhancers That Are Rmentioning
confidence: 80%
“…4f). This transient induction became even more apparent when we called H3K27ac peaks in two recent, independent iPSC reprogramming studies [74,75] (Fig. 4h-i).…”
Section: Starr-seq Reveals Endogenous Retrovirus Enhancers That Are Rmentioning
confidence: 80%
“…Defined cocktails of transcription factors (TFs) are capable of interconverting cell types from different lineages and to reprogram somatic donor cells to self-renewing pluripotent cells 13 . The induction of pluripotent stem cells (iPSCs) from fibroblasts by Oct4, Sox2, Klf4, and c-Myc (OSKM) is a widely used model system to study the underlying molecular mechanisms of cell fate conversion 48 . Reprogramming-capable TFs originate from diverse structural families without any obvious evolutionary relationship, and even closely related factors can vary widely in their reprogramming competency.…”
Section: Introductionmentioning
confidence: 99%
“…We then obtained the genomic binding sites (peaks) of the 23 lncRNAs from the aforementioned experiments, and found the ratio of this overlap from published data ( Figure 2G ) is highly correlated with the corresponding PIRCh-seq signal among most of the lncRNAs ( Figure 2H ). The Spearman correlation coefficients of the ratio of the overlap ChIP-seq peaks 39 with the lncRNA’s PIRCh-seq enrichment scores in the same cell line were significantly higher than random permutations ( Figure 2I , P <0.0001). These results further confirm that PIRCh-seq reliably identifies chromatin associated lncRNAs.…”
Section: Resultsmentioning
confidence: 92%
“…We found a total of 23 expressed lncRNAs in the LnChrom database, including Xist, Firre, Rmrp, Tug1 and etc., and all of them were positively enriched in our PIRCh experiment and 14 of which were significant with P-value<0.05, suggesting the high sensitivity of the PIRCh approach in identifying chromatin associated lncRNAs. Furthermore, we obtained the genomic binding sites (peaks) of 23 lncRNAs from the aforementioned experiments, and overlapped them with the histone ChIP-seq peaks 12 and got a ratio of the overlap for each lncRNA. We then calculated the Spearman correlation coefficients of these ratios with their corresponding lncRNA’s PIRCh-seq enrichment scores in the same cell line (normalized by the total number of different ChIP-seq peaks), and found that these correlations were significantly higher than random permutations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation